Natural Apocarotenoids and Their Synthetic Glycopeptide Conjugates Inhibit SARS-CoV-2 Replication - Ilona Bereczki; Henrietta Papp; Anett Kuczmog; Mónika Madai; Veronika Nagy; Attila Agócs; Gyula Batta; Márton Milánkovits; Eszter Ostorházi; Ana Mitrović; Janko Kos; Áron Zsigmond; et al. (MDPI AG, 2021)
The protracted global COVID-19 pandemic urges the development of new drugs against the causative agent SARS-CoV-2. The clinically used glycopeptide antibiotic, teicoplanin, emerged as a potential antiviral, and its efficacy was improved with lipophilic modifications. This prompted us to prepare new lipophilic apocarotenoid conjugates of teicoplanin, its pseudoaglycone and the related ristocetin aglycone. Their antiviral effect was tested against SARS-CoV-2 in Vero E6 cells, using a cell viability assay and quantitative PCR of the viral RNA, confirming their micromolar inhibitory activity against viral replication. Interestingly, two of the parent apocarotenoids, bixin and β-apo-8'carotenoic acid, exerted remarkable anti-SARS-CoV-2 activity. Mechanistic studies involved cathepsin L and B, as well as the main protease 3CLPro, and the results were rationalized by computational studies. Glycopeptide conjugates show dual inhibitory action, while apocarotenoids have mostly cathepsin B and L affinity. Since teicoplanin is a marketed antibiotic and the natural bixin is an approved, cheap and widely used red colorant food additive, these readily available compounds and their conjugates as potential antivirals are worthy of further exploration.